Cocaine use in America : epidemiologic and clinical perspectives - Kozel, Nicholas J., ed. (US Department of Health and human Services Washington DCUS, 1985)
Papers present state and results of research on patterns and consequences of cocaine use and abuse in the United States. Discusses cocaine use in the household population, among adolescents and young adults. Outlines characteristics of cocaine abusers and discusses psychiatric diagnosis by route of administration of the drug. Gives overview of treatment perspectives and makes recommendations for management of cocaine dependence.